Study on the policy implementation effect of serious Illness medical insurance in the ethnic minority autonomous area of Western China - Jiang, Nan; Promasatayaprot, Vorapoj; Leethongdissakul, Songkhamchai; Da Gao, Hong (Acta Bioethica, 2024)
Objective: To evaluate the implementation effect of serious illness medical insurance in Guang Xi Zhuang Autonomous Region of western China. Study design: Through the collection of 2017-2021 Guang Xi serious illness medical insurance specific policy making such as fund usage, serious illness compensation, medical expenses data, and data analysis of a serious illness medical insurance effect. Method: Literature research, Policy text analysis, quantitative data collection method, using Excel and SPSS 19.0 data descriptive statistical analysis and comparative analysis. Results: Serious illness medical insurance has had some effect, e.g., from 2017 to 2021, the utilization rate of serious illness medical insurance fund in Guang Xi was 109.49% and 103.87% respectively, the fund balance rate was -9.45% and -8.54% respectively, and the accumulated balance was -2.3871 million CNY and -70.7955 million CNY. Conclusion: The serious illness medical insurance has reduced the burden of large medical expenses of patients to a certain extent, but the fund is under too much pressure, and there is a payment deficit. The coverage and security of serious illness medical insurance need to be expanded and strengthened, and the cooperation mechanism with commercial insurance institutions should be gradually explored to improve the serious illness medical insurance.